2015
DOI: 10.1371/journal.pone.0126269
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Peripheral Blood Monocyte-to-Lymphocyte Ratio Predicts Poor Prognosis in Patients with Primary Pulmonary Lymphoepithelioma-Like Carcinoma

Abstract: Primary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare type of non-small cell lung cancer. In this study, we retrospectively reviewed the data from 74 consecutive patients with pulmonary LELC and investigated the prognostic value of pretreatment monocyte-to-lymphocyte ratio (MLR). The cut-off value determined by ROC curve for MLR was 0.262. According to this cut-off value, 36 (48.6%) patients had lower MLR value (<0.262) at diagnosis. There was no significant correlation between MLR level and gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…Patients with only one of these abnormal levels were given a score of 1 12 . BMI, CAR, and LMR were categorized into two groups according to the cutoff values of ≥18.5 kg/m 2 , ≥0.5, and ≥3.82, respectively 9 , 37 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients with only one of these abnormal levels were given a score of 1 12 . BMI, CAR, and LMR were categorized into two groups according to the cutoff values of ≥18.5 kg/m 2 , ≥0.5, and ≥3.82, respectively 9 , 37 , 38 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Markovic et al [35] reported a non-significant result for DLBCL (HR: 0.70, 95% CI: 0.40–1.23; P = 0.212) (Figure 5A). Eighteen studies comprising 5,805 patients reported hazard ratios for PFS [15, 16, 28, 31, 36, 39, 41, 42, 46, 48, 50, 52, 54, 57–60, 62]. The effect of LMR on PFS among cancer subgroups is presented in Figure 5B.…”
Section: Resultsmentioning
confidence: 99%
“…LELC patients exhibited superior OS; the therapeutic outcome was also improved than the other two subtypes, and LELC was considered as an independent factor for prognosis (14). It was reported that the 2-year OS for different observations with 35, 52, and 74 LELC patients was 81%, 88%, and 86%, respectively, while the 5-year OS was 51%, 62%, and 72%, respectively (9,13,27). Moreover, the 5-year PFS and OS were 68% and 79%, respectively for the reports from Jiang et al based on 79 LELC patients (28).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the prognosis of LELC was satisfactory. An improved OS could be found in the patients with the tumor at an early stage, without lymph node metastasis, and radical resection (13); the OS and DFS were worse for patients at the advanced stage of the tumor (27). It was reported that smoking (11) and staging of the tumor (11,28) were the two independent factors influencing OS as analyzed by COX regression; whereas, the diameter and the staging of the tumor (28) were the independent factors influencing DFS.…”
Section: Resultsmentioning
confidence: 99%